Controller design of unicycle mobile robot - Ab Rashid, Mohd Zamzuri; Sidek, Shahrul Na'im (IIUM Press, 2012)
The ability of unicycle mobile robot to stand and move around using one wheel has attracted a lot of researchers to conduct studies about the system, particularly in the design of the system mechanisms and the control strategies. This paper reports the investigation done on the design of the controller of the unicycle mobile robot system in maintaining its stability in the longitudinal and lateral directions. The controller proposed is a Linear Quadratic Controller (LQR) type which is based on the linearized model of the system. A thorough simulation studies to find out the performance of the LQR controller have been carried out. The best controller gain, K acquired through the simulation is selected to be implemented and tested in the experimental hardware. Finally, the results obtained from the experimental study are compared to the simulation results to study the controller efficacy. The analysis shows that the proposed controller design is able to stabilize the unicycle mobile robot.